Intraoperative lung edema monitoring by microwave reflectometry - Nowak, Kai; Gross, Wolfgang; Nicksch, Kathrin; Dacho, Christine; Helbig, Marko; Hohenberger, Peter; Gebhard, Martha-Maria; Schäfer, Michael (Interactive cardiovascular and thoracic surgery, 2011)
Microwave reflectometry might be a suitable tool for the thoracic surgeon to monitor edema formation of the lung during lung surgery. A new setup of microwave reflectometry for lung water measurements was developed and tested for clinical application. Three lung models were used for the microwave reflectometry tests: 1) the model of an ex vivo isolated perfused rat lung to investigate lung edema formation during ischemia-reperfusion (n=6), 2) the in situ lung of a human patient to demonstrate the feasibility of lung water monitoring during a surgical operation, 3) the model of an ex vivo isolated perfused human lung to investigate edema formation during postischemic reperfusion and to investigate the changes in water content in the region of a tumor. During human lung operation, significant changes in water content occurred in different lung areas. During isolated perfusion, a significant increase in lung water was measured in models 1) and 3) (P=0.03). Water content of tumor tissue was higher than in the surrounding healthy lung tissue. Microwave reflectometry offers a noninvasive approach to monitor lung edema formation in experimental models and during thoracic surgery.